Effective playing time affects technical-tactical and physical parameters in football - Tojo, Óscar; Spyrou, Konstantinos; Teixeira, João; Pereira, Paulo; Brito, João (Frontiers in Sports and Active Living, 2023)
Effective playing time has been debated as a topic of major concern in football. Thus, the current experimental study aimed to investigate the effects of effective playing time on technical-tactical and physical match parameters in football. One hundred and seventy-nine male highly trained football players (aged 27.9 ± 5.1 years) from twelve teams performed two different match-play conditions: 45 minutes of match-play without stopping the chronometer (T45), and 30 minutes of match-play by stopping the chronometer every time the ball was out-of-play (T30). T30 presented a significantly higher total time (49:30 vs 45:00 min; p=<.001; ES=0.76), effective playing time (28:70 vs 26:80 min; p=<.001; ES=0.62), and stopped time (20:60 vs 18:20 min; p=0.003; ES=0.38) compared to T45. Total ball possession (54.4% vs 45.6%; p=0.002) and 1/3 ball possession (55.3% vs 44.7%; p=0.018) was higher in T30 condition when compared to T45. Regarding match external load, total distance covered (4899 vs 4481 m; p=<.001; ES=0.71), moderate-speed running (607 vs 557 m; p=0.002; ES=0.26) and high-speed running (202 vs 170 m; p=<.001; ES=0.33), high-speed activities (284 vs 245 m; p=0.003; ES=0.24), accelerations (27 vs 24; p=<.001; ES=0.32), and decelerations (31 vs 28; p=0.005; ES=0.26) were higher in T30 compared to T45. In conclusion, these findings suggest that higher effective playing time may affect technical-tactical and physical parameters during football games.